PENGARUH LINGKUNGAN SEKOLAH TERHADAP MINAT BELAJAR SISWA MATA PELAJARAN PKN KELAS 3 DI SDN 009 PADANG KUNIK - Julindri; Laili Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to describe the influence of the school environment on students' interest in learning Civics subjects in Grade 3 at SDN 009 Padang Kunik. The research method used is quantitative descriptive. The population used in this study was 7 students. The sampling method used was the non-probability sampling method, namely saturated saturated samples. So the entire population is the sample in this study. Data were collected through questionnaires and documentation. The research instruments were tested, namely tests (normality and homogeneity tests), descriptive analysis and hypotesis tests. Based on the results of the study, it can be seen that the regression equation obtained is Y = (310,565) + 2087X with a regression coefficient of 2087 and a T value = 1860, this indicates that each unit in the school environment will increase students' interest in learning by 1860 units. So it can be concluded that the partial T test research that is accepted, the partial T test is partial Ho is rejected and partial T Ha is accepted. So it can be concluded that there is an influence between the school environment and students' interest in learning.